Transduction of Gal(+) by Coliphage T1 II. Role of λ Transcription Control in the Efficiency of Transduction - Drexler, Henry (1972)
One of the crossovers leading to the transduction of Escherichia coli W3350 or one of its derivatives for the Gal(+) marker by T1 grown on donors lysogenic for λ must occur to the right of the galactose operon. The location of this crossover determined both the rate of transduction and the λ genes which control the transduction by (λ-gal)T1. When the crossover occurred either to the left of gene N or the right of the cI gene, it was affected in a positive fashion by the gene product of the N(+) gene. When the crossover occurred either to the left of gene N or between N and gene Q, its efficiency was not significantly affected by the expression of Q(+). However, crossovers to the right of gene Q were greatly stimulated by the presence of a functioning Q gene on the chromosome of (λ-gal)T1 hybrid. The repressor made by the cI(+) gene of λ blocked efficient transduction. Therefore, the control of efficient transduction by (λ-gal)T1 is the same as the control of transcription of λ. It is concluded that the increased efficiency of transduction by (λ-gal)T1 in nonimmune recipients is not caused by any particular product of a gene but rather by the process of transcription itself.